THE EFFECT OF THE INQUIRY MODEL ON SCIENCE COMPETENCY OF CLASS 8 STUDENTS OF THE MOVEMENT SYSTEM MATERIAL IN THE LIVING CREATURES OF THE STATE JUNIOR HIGH SCHOOOL 1 - messy apsari; Skunda Diliarosta (Department of Science Education, 2021)
The purpose of this study was to determine the effect of the inquiry learning model on the knowledge competence of grade VIII students about the material of motion systems in living things at SMP Negeri 1 Basa Ampek Balai Tapan. This research was conducted at SMP Negeri 1 Basa Ampek Balai Tapan Academic Year 2020/2021. This type of research is quasi-research (Quasy Experient Research). The research design used was The Non Equevalent Control Group. The sample in this study was 15 people for each control and experimental class. The sampling technique used purposive sampling. Class VIII.1 as the experimental class used the inquiry model and class VIII.3 class as the control class used the conventional learning model (lecture). The instrument used was this research using a written test. Data analysis used t test at a significance level of 0.05, with the prerequisite test for normality and homogeneity. Hypothesis testing using the t test, the results of statistical calculations obtained the price of t count of 2.840> t table of 1.753 with a significance level of 0.008 ˂ 0.05. Thus Ho was rejected and Ha accepted. This shows that there is a significant effect of the inquiry model on students' knowledge competencies.